Functional rehabilitation for patients affected by covid-19 - De Souza, Júlio César; Ferreira, Joel Saraiva; De Souza, Geize Rocha Macedo (Revista Cuidarte, 2021)
The SARS-CoV-2 virus was detected in the city of Wuhan, China, at the end of 2019. Since then, the high transmissibility of this new coronavirus and the high morbidity and mortality related to COVID-19, the viral infection caused by SARS-CoV- 2, has grown exponentially across the planet, culminating first in a public health emergency of international importance and then in a serious pandemic. The transmission of the virus occurs both through respiratory and extra-respiratory ways and during the period of development of COVID-19 in the human body, the clinical presentation includes symptoms related to changes in smell, taste and gastrointestinal complications, in addition to more severe involvement of the respiratory system . As a result of the symptoms of COVID-19, many patients need to be hospitalized and, in some cases, undergo invasive procedures to ensure the basic physiological condition for the maintenance of life. During the hospitalization period, patients develop a clinical condition with physiological debilitation and general physical fitness significantly reduces. Upon being discharged from hospital, many of these patients need treatments aimed at recovering the physical condition weakened by the action of the disease. The Municipal Department of Public Health (SESAU) of Campo Grande/MS, in the Center-West Region of Brazil, was attentive to this demand. The Non-Communicable Chronic Diseases Service (DANT), together with the Specialized Care Coordination, structured a functional rehabilitation service in the Unified Health System (SUS) for people with chronic non-communicable diseases who were hospitalized for SARS- CoV-2 and need specialized attention to restore the ability to work and carry out activities of daily living. The service is provided at the Specialized Rehabilitation and Diagnosis Unit (UERD), which is part of the Municipal Health Network (REMUS). A functional rehabilitation project was elaborated by the technical team of SESAU, to be developed through a multidisciplinary team formed by a physiotherapist, a physical education professional, a nutritionist and a psychologist. Interventions are carried out using Unique Therapeutic Projects (PTS), following pre-established inclusion and exclusion criteria, for patients with chronic non-communicable diseases, in post-hospitalization conditions resulting from COVID-19. The referral of patients from other REMUS points is carried out by physicians from the three levels of health care (primary, secondary and tertiary), via the Regulation System (SISREG). How to cite this article: De Souza, Júlio César; Ferreira, Joel Saraiva; De Souza, Geize Rocha Macedo. Reabilitação funcional para pacientes acometidos por covid-19. Revista Cuidarte. 2021;12(3):e2276. http://dx.doi.org/10.15649/cuidarte.2276